2019
DOI: 10.5603/ep.a2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone imbalance on colorectal cancer carcinogenesis and risk — a systematic review

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer-related death. The prevalence of colorectal neoplasm is increasing. Many studies have shown that thyroid dysfunction may be connected with the higher risk of pancreatic and breast cancer, but only a few described the role of thyroid dysfunction and thyroid hormone (TH) replacement in the development and risk of CRC. The aim of this study is to summarise all findings and potentially elucidate the connection between TH imbalance and colorectal cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At the same time increased TSH level is associated with poor prognosis for endometrial carcinoma patients [ 117 ]. A meta-analysis study reported an elevated risk of colorectal cancer in patients with hypothyroidism and thyroid replacement therapy has a protective role [ 118 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…At the same time increased TSH level is associated with poor prognosis for endometrial carcinoma patients [ 117 ]. A meta-analysis study reported an elevated risk of colorectal cancer in patients with hypothyroidism and thyroid replacement therapy has a protective role [ 118 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…Truncated TRΔβ3 lacks the DNA binding domain but retains T 3 binding activity and acts as a dominant-negative antagonist, similar to TRΔα1 and TRΔα2 (6)(7)(8)(9). Several studies to date have reported aberrant expression and/or somatic mutations of TR in human cancers (3,(10)(11)(12)(13)(14)(15)(16)(17)(18), including hepatocellular carcinoma (HCC) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, hyperthyroidism is correlated with cancer prevalence in various cancer types, including liver, thyroid, brain, breast, lung, and colorectal cancer [ 44 , 45 ]. However, no such relationship between autoimmune hyperthyroidism and lung cancer was found in our Mendelian study.…”
Section: Discussionmentioning
confidence: 99%